Implementation of Islamic Religious Education Learning Media for Zakat Material in Improving Zakat Understanding at Al-Ma'arif NU Merauke Middle School - Syamsul Qomar; Shofwan Al Jauhari; Hendra Yulia Rahman (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Research on the implementation of PAI Zakat Material learning media to increase Zakat Understanding at Al-Ma'arif Middle School NU Merauke is intended to describe the implementation of PAI Zakat Material learning media, obstacles and solutions faced by teachers when implementing the learning media provided by teachers when implementing PAI learning media Zakat material at Al-Ma'arif Middle School NU Merauke. This research is included in the qualitative descriptive research. Data collection was carried out using observation, interview, and documentation methods. To analyze, analysis is carried out during data collection, namely inductively using descriptive data through systematic logical reasoning on the data (data validity) and data analysis after the data is collected using triangulation techniques (comparing/examining, checking the validity of the data) with the results of interviews and content results. From the results of this research, it can be concluded that what was done by the author can be seen, (1) the implementation of PAI Zakat Material learning media to increase the Understanding of Zakat at Al-Ma'arif Middle School NU Merauke in the learning process is the planning stage, implementation stage, implementation in class, (2) the obstacles and solutions faced by teachers when applying learning media to PAI subjects. Zakat material is limited preparation time when a teacher provides material about PAI, the lights often go out when the learning process takes place in the classroom, it is difficult to find VCDs related to the learning material. Appropriate PAI, Drowsiness in class, using (earphones) to listen to music/radio during the learning process, Environmental/indoor conditions, students' lack of speed in understanding the material, and different levels of student intelligence. To overcome obstacles in implementing PAI learning media Zakat Material in Increasing Understanding of Zakat at Al-Ma'arif Middle School NU Merauke what is done is to understand the characteristics of students, by approaching students directly, adjusting students' abilities in using strategies or methods and learning media.